Analisis Membangun Budaya Kerja yang Positif Untuk Dapat Meningkatkan Loyalitas Terhadap Karyawan - Lucki Hidayanto; Enjum Jumhana; Dendi Subardi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The existence of a positive work culture has a very important role in increasing loyalty towards employees in a company. A very supportive work environment and effective communication can create a very conducive culture. This research aims to analyze how a positive work culture can influence employee loyalty. And what strategies can be implemented in a company that aims to build a better work environment. By implementing a positive work culture, this company can increase employee retention and create an effective environment.